(untitled) (Development Service Industry Management, 2024)
The study examines the main aspects of the impact of artificial intelligence (AI) on the economic growth of modern societies. It focuses on technological innovations caused by the development of AI and their role in increasing the productivity and efficiency of economic processes. Significant attention is paid to data analysis and forecasting as key factors contributing to the optimization of business operations and strategic decision-making. The study demonstrates how the automation of routine tasks and the introduction of intelligent systems can reduce costs and increase productivity. The study also examines examples of successful AI applications in various industries, including finance, healthcare, manufacturing, and logistics. This makes it possible to assess the extent of the impact of the latest technologies on the economic environment and the competitiveness of enterprises. An important component of the study is the analysis of the challenges and risks associated with the introduction of AI, including the issue of unemployment due to job automation and the ethical aspects of using technology. The author suggests possible ways to overcome these problems, in particular by improving the skills of workers and creating new jobs in industries that are developing thanks to AI. The author offers conclusions on the prospects for further development of AI and its potential impact on the global economy. The author emphasizes the need for active involvement of the public and private sectors in the process of integrating AI into all sectors of the economy in order to ensure sustainable development and economic growth.